Personalised medicine for non-classic cystic fibrosis resulting from rare CFTR mutations. Issue 1 (30th July 2020) - McCravy, Matthew S.; Quinney, Nancy L.; Cholon, Deborah M.; Boyles, Susan E.; Jensen, Timothy J.; Aleksandrov, Andrei A.; Donaldson, Scott H.; Noone, Peadar G.; Gentzsch, Martina
Cystic fibrosis (CF) is a monogenetic disorder of the CFTR gene that has traditionally been associated with Caucasian people. While accounts of syndromes, likely caused by CF, have been identified dating back to the 16th century, the physiological basis of the disease at the cellular and genetic levels was not clarified until the 1980s [1, 2]. Since that time over 2000 mutations in the CF transmembrane conductance regulator (CFTR) have been identified [3]. While the majority (∼80%) of patients are diagnosed within the first 2 years of life, about 10% of patients present in adulthood, and some patients present at an advanced age [4]. Using a precision medicine approach to define a rare CFTR mutation, we demonstrated that CF patients with this mutation may benefit from available therapies. This study illustrates the power of laboratory techniques for optimising patient treatments. https://bit.ly/2WtBHiL